Development of patient-practitioner assistive communications (PPAC) ontology for type 2 diabetes management - Forbes, David; Wongthongtham, Pornpit; Singh, Jaipal (CEUR-WS.org, 2012)
Communication in primary care is a key area of healthcare slow to adopt new technology to improve understanding between the patient and healthcare practitioner. Patients whose cultural background and regular form of dialectal communication are far removed from that of mainstream society are particularly disadvantaged by this during the patient-practitioner interview encounter (PPIE). In this paper, we present an assistive communications technology (ACT) framework for PPIE developed using a Type-2 Diabetes Management Patient-Practitioner Assistive Communications (T2DMPPAC) ontology in order to help both Aboriginal patient and non-Aboriginal practitioner optimise their pre-encounter, during-encounter and post-encounter communication. The T2DMPPAC architecture provides knowledge and presents it in a manner that is easily accessible and understood by the user (patients and practitioners) as well as accompanying carers, and as appropriate, interpreters. An example of bi-directional mapping of concepts to language during a PPIE session is shown using the ontology.